1999
DOI: 10.1111/j.1741-6248.1999.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring in Family Firms: A Reflective Analysis of Senior Executives' Perceptions

Abstract: This study is a reflective analysis of the perceptions of senior executives in family businesses that relate to their personal experiences of having been mentored. The study presents an overview of the topic of mentoring, defines key terms, and identifies questions addressed in the research. The rationale for this study rested on two facts.First, mentoring in non-family businesses constitutes the majority of the literature. That literature supports the importance of mentoring. Secondly, mentoring in family bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 27 publications
0
49
0
3
Order By: Relevance
“…For this reason, different research studies address the role of career development, outside work experiences, apprenticeship, on-the-job training, formal education, and the role of training programs in the process of preparing and developing a competent leader (for references, see [41]). The role of mentoring and the selection of mentoring techniques in family firms were explored by [4]. [47] addressed the issue of training of the next-generation family members after they joined the management team; their findings indicated that involving next-generation family members in the strategic planning process brings benefits to their development.…”
Section: Effectiveness Of Family Business Successionmentioning
confidence: 99%
“…For this reason, different research studies address the role of career development, outside work experiences, apprenticeship, on-the-job training, formal education, and the role of training programs in the process of preparing and developing a competent leader (for references, see [41]). The role of mentoring and the selection of mentoring techniques in family firms were explored by [4]. [47] addressed the issue of training of the next-generation family members after they joined the management team; their findings indicated that involving next-generation family members in the strategic planning process brings benefits to their development.…”
Section: Effectiveness Of Family Business Successionmentioning
confidence: 99%
“…These findings suggest that many knowledge creation processes and activities during the succession are going on informally and spontaneously or even blind. Such informal processes have clearly certain benefits (e.g., flexibility and establishing caring relationship), but on the other hand the lack of clear objectives and agenda can lead to lower level of productivity (e.g., Boyd et al, 1999). This confirms the need of preparing written plan of succession where the major part should cover successor's training and his/hers involvement in the organizational knowledge creation process within a family business.…”
Section: Discussionmentioning
confidence: 96%
“…In our research in only one case (the case no.4) the mentoring was done by the external expert indicating the preference of family business leader's mentoring. Boyd et al (1999) found strong preference of informal mentoring by a family member in family businesses. This kind of mentoring has numerous strengths (e.g., flexibility, unforced, unstructured, opening up communication and establishing caring relationship).…”
Section: Knowledge Creation During Family Business Successionmentioning
confidence: 94%
See 2 more Smart Citations